EFEKTIVITAS PROGRAM PEMUTIHAN DENDA PAJAK DAN BEA BALIK NAMA KENDARAAN BERMOTOR DI KOTA SUKABUMI - Nur, Tuah; Silfia Rani, Indri; Firmansyah, Dhani; Permatasari, Utari (LPPM UNSAP & FISIP UNSAP, 2024)
This research on the Effectiveness of the Tax and Vehicle Title Fee Bleaching Program at the Sukabumi City Samsat Office was conducted due to the large number of delinquent taxpayers. This study uses Duncan's theory of effectiveness with the dimensions of goal achievement, integration and adaptation. The purpose of this study was to determine the effectiveness of the Bleaching Program for Tax Fines and Vehicle Title Transfer Fees in Sukabumi City. In this study the authors used a descriptive qualitative approach to explain and interpret the process or experience related to the bleaching program. Based on the results of research conducted related to the bleaching program, it can be concluded that the bleaching program in Sukabumi City has not been effective. Thus, there is a need for further effective socialization and cooperation or collaboration with police agencies to increase taxpayer awareness in providing information related to the bleaching program.